Penerapan Posisi Semi Fowler terhadap Peningkatan Status Pernapasan pada Pasien Pneumonia dengan Respiratory Failure Diruang ICU RSD Gunung Jati Kota Cirebon - Sri Sundari; Erida Fadila; Dwiyanti Purbasari (CV. ALIM'SPUBLISHING, 2026)
Pneumonia with respiratory failure is a critical condition caused by inflammation of the lung parenchyma that disrupts gas exchange, requiring intensive care in the ICU. In addition to medical therapy, an effective non-pharmacological intervention to optimize lung expansion and oxygenation status is the semi-Fowler position (30°–45°). Objective: To analyze the effectiveness of the semi-Fowler position in improving respiratory status in pneumonia patients with respiratory failure in the ICU of Gunung Jati Regional Hospital, Cirebon City. Methods: This study used a descriptive case study method based on evidence-based practice. Subjects consisted of five adult patients with respiratory failure in the ICU. The semi-Fowler position intervention was given for 3 consecutive days of care. The instruments used included a critical care nursing care format, an oximeter, and an observation sheet. Results: Before the intervention, all five patients experienced severe shortness of breath with an average respiratory rate (RR) of 26–30 x/minute. The primary patient (Mrs. I, 74 years old) experienced decreased consciousness, was on a ventilator, had accumulated secretions, and rhonchi. After 3 days of semi-Fowler position intervention accompanied by adequate suctioning, all five patients showed significant improvement with a decrease in RR of 5–6 x/minute (to 20–25 x/minute). In Mrs. I, the accumulation of secretions and rhonchi decreased, peripheral circulation improved, and there were no pressure ulcer complications. Conclusion: The application of the semi-Fowler position (30°–45°) effectively improved respiratory status and addressed the nursing problem of ineffective breathing patterns in pneumonia patients with respiratory failure in the ICU.